The Effect of Red & Blue Rich LEDs vs Fluorescent Light on Lollo Rosso Lettuce Morphology and Physiology - Cammarisano, Laura; Donnison, Iain S.; Robson, Paul R. H. (Frontiers in Plant Science, 2021)
The challenges of feeding an increasing population, an increasingly urban population and within an increasingly challenging global environment have focussed ideas on new ways to grow food. Growing food in a controlled environment (CE) is not new but new technologies such as broad-spectrum LEDs and robotics are generating new opportunities. Growth recipes can be tailored to plant species in a CE and plasticity in plant responses to the environment may be utilised to make growth systems more efficient for improved yield and crop quality. Light use efficiency within CE must consider energy requirements, yield and impacts on quality. We hypothesised that understanding how plants change their morphology and physiology in response to light will allow us to identify routes to make light more efficient for delivery of high-quality produce. We focussed on responses to light in Lollo rosso lettuce which produces compact, crinkly and highly pigmented leaves. We compared the spectra of the commonly used artificial light sources in indoor farming (compact fluorescence tubes, FL, and broad-spectrum light-emitting diodes, LEDs) at two irradiance levels (270 and 570 μmol m‐2 s‐1). We discovered LEDs (λP: 451, 634 and 665 nm) produced the same amount of produce for half the incident energy of FL (T5). At higher irradiances LEDs produced 9% thicker leaves, 13% larger rosettes and 15% greater carotenoid content. Leaves differed in light absorptance with plants grown under lower FL absorbed 30% less of mid-range wavelengths. We show that the relative efficiencies of LED and FL is a function of the irradiances compared and demonstrate the importance of understanding the asymptotes of yield and quality traits. Increasing our understanding of structural and biochemical changes that occur under different combination of wavelengths may allow us to better optimise light delivery, select for different ranges of plasticity in crop plants and further optimise light recipes.